Opus 1 the artist's beginnings - Lindmayr, Ulrike; Pültau, Dirk 1964- (Roma Publ., 2015)
Whenever we set out to tackle an artist's oeuvre we generally try to trace the "decisive moments", the turning points, the interruptions, the final work. There is one "key moment", however, that seems virtually to guarantee the ultimate understanding of the oeuvre, its beginning, its Opus 1. It is not without some justification that the inception of the oeuvre or artistic activity is surrounded by myth and mystification. As will appear time and time again in this book, the oeuvre and the Opus 1 are "constructions". Whatever one regards as the oeuvre and whichever Opus 1 is pointed out, those choices are always based on a predetermined and well-defined image of the artist's production
Aus dem Niederländ. übers. - Bibliogr. Angaben von S. 207
Keywords: Geschichte; Künstler; Erstlingswerk; Kunst; Konferenzschrift -- 2009 -- Antwerpen